LOBBYING IN THE EU POLICY-MAKING ARENA - NISTOR, Camelia (Studia Universitatis Babeș-Bolyai Ephemerides, 2015)
Lobbying is part of a democratic political life. Today, EU lobbying, which is extremely active in democratic systems, is considerably more structured, institutionalized and regulated than at the beginning of the European construction. It represents an essential component of the relation between decision-makers and interest groups based on the citizens’ fundamental right to bring their contribution to the policy-making process. Governmental actors need expertise for creating and implementing public policies, while interest groups need access to key decision-makers aiming to influence political decisions. In this article, the author proposes an analysis of lobbying and EU policy-making as the relations between decision-makers and different interest groups are essential for developing a more transparent and efficient decision-making process.